An examination of the relationship between kindergarten children's gender and knowledge of basic relational concepts [Anasinifina devam eden çocuklarin cinsiyetlerine göre temel iliskisel kavram bilgilerinin incelenmesi] - (:unkn) unknown (My University, 2009)
This study investigated young children's knowledge of basic relational concepts in relation to their gender. Randomly selected 154 young children from different schools participated in this study. The mean age of children was 66.20 months with a standard deviation of 5.91. The Boehm Tests of Basic Concepts for children (Boehm-3, 2000) was administrated to the children individually. The results revealed that girls performed on "little-some, double-pair and backward" concepts and the boys performed on "little-some, the widest and skip" concepts below 50% achievement level. Statistically significant differences on the total concept scores of the girls and the boys were not observed (p>.05). Similarly, regarding the gender, statistically significant differences on the total basic concept scores of the children who have brothers or sisters, and those having no brothers or sisters were not seen. However; single children received higher total concept scores. It was also observed that mothers' level of education was related only to girls' knowledge of basic relational concepts, but father's education level was related both to boys' and girls' concepts of information level.
Keywords: Basic relational concept information; Boehm-3; Demographic information; Kindergarten